Metabolite profiling of Aquilaria malaccensis leaf extract using liquid chromatography-Q-TOF-mass spectrometry and investigation of its potential antilipoxygenase activity in vitro. - Eissa, Manar; Hashim, Yumi Zuhanis Has-Yun; El-Kersh, Dina; Syed Abd Azizz, Saripah Salbiah; Mohd Salleh, Hamzah; Md Isa, Muhammad Lokman; Abd Warif, Nor Malia (MDPI, 2020)
The Aquilaria malaccensis species of the genus Aquilaria is an abundant source of agarwood resin and many bioactive phytochemicals. Recent data regarding the chemical constituents and biological activities of Aquilaria leaves led us to attempt to qualitatively profile the metabolites of Aquilaria malaccensis leaves from a healthy, noninoculated tree through phytochemical screening, GC‐MS, and LC/Q‐TOF‐MS. The present work is also the first to report the antilipoxygenase activity of A. malaccensis leaves from healthy noninoculated tree and investigate its toxicity on oral mucosal cells. A total of 53 compounds were tentatively identified in the extract, some of which have been described in literature as exhibiting anti‐inflammatory activity. A number of novel compounds were identified for the first time, including quercetin, quercetin‐O‐hexoside, kaempferol‐O‐ dirhamnoside, isorhamnetin‐O‐hexoside, syringetin‐O‐hexoside, myricetin, tetrahydroxyflavanone, hesperetin, sissotrin, and lupeol. The antilipoxygenase assay was used to determine the lipoxygenase (LOX) inhibitory potential of the extract, while a WST‐1 assay was conducted to investigate the effect of the extract on oral epithelial cells (OEC). The extract implied moderate anti‐LOX activity with IC50 value of 71.6 μg/mL. Meanwhile, the cell viability of OEC ranged between 92.55% (10 μg/mL)–76.06% ± (100 μg/mL) upon treatment, indicating some potential toxicity risks. The results attained encourage future studies of the isolation of bioactive compounds from Aquilaria malaccensis leaves, as well as further investigation on the anti‐ inflammatory mechanisms and toxicity associated with their use.